Functional disability among elderly patients attending the General Outpatient clinics of Usmanu Danfodiyo University Teaching Hospital, Sokoto, Nigeria - Sada. A. Yahanazu (Nigerian Frontline Medicine Journal, 2024)
Background: Population ageing is allied to an increase in chronic diseases and decreased functional independence. This study was conducted to assess the functional status of elderly patients attending the General Outpatient Clinic of Usmanu Danfodiyo Teaching Hospital, Sokoto, Nigeria.